2021
DOI: 10.3390/antiox10050787
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin and Isorhamnetin Attenuate Benzo[a]pyrene-Induced Toxicity by Modulating Detoxification Enzymes through the AhR and NRF2 Signaling Pathways

Abstract: Benzo[a]pyrene, classified as a Group 1 carcinogen, is metabolized to B[a]P-7,8-dihydrodiol-9,10-epoxide (BPDE), causing DNA mutations and eventually cancer. Quercetin is a dietary flavonoid abundant in fruits and vegetables. After quercetin intake, quercetin’s metabolites isorhamnetin and miquelianin are more highly concentrated than quercetin in the human plasma. In this study, we investigated the molecular mechanisms associated with the cytoprotective effect of quercetin and its metabolites against benzo[a]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 49 publications
(53 reference statements)
2
31
0
Order By: Relevance
“…In the present study, we investigated the role of alpinetin in macrophage/endothelial adhesion and monocyte intimal infiltration, and we analyzed its protective function in the development of atherosclerotic plaques. Given that other flavonoids, such as narigenin, 25 epicatechin, 26 and quercetin, 27 have been demonstrated to enhance antioxidant defense by regulating Nrf2, and that puerarin 28 and procyanidin 29 are effective GSK‐3β modulators, we further explored whether the beneficial effects of alpinetin are dependent on GSK‐3β/Nrf2‐mediated redox restoration.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we investigated the role of alpinetin in macrophage/endothelial adhesion and monocyte intimal infiltration, and we analyzed its protective function in the development of atherosclerotic plaques. Given that other flavonoids, such as narigenin, 25 epicatechin, 26 and quercetin, 27 have been demonstrated to enhance antioxidant defense by regulating Nrf2, and that puerarin 28 and procyanidin 29 are effective GSK‐3β modulators, we further explored whether the beneficial effects of alpinetin are dependent on GSK‐3β/Nrf2‐mediated redox restoration.…”
Section: Introductionmentioning
confidence: 99%
“…[ 28 ]. Moreover, several studies found that quercetin supplementation could significantly reduce hepatotoxicity and nephrotoxicity caused by antibacterial drugs (e.g., rifampicin and ciprofloxacin) or environmental toxins (e.g., copper, nickel, ochratoxin A, and benzo(a)pyrene) by inhibiting oxidative stress and the inflammatory response [ 29 , 30 , 31 , 32 , 33 ]. Currently, there is limited information on whether quercetin could provide the protective effects on QCT-induced cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Recent studies indicated that flavonoids (e.g., quercetin) can lower B[a]P-induced toxicity by increasing the expression of phase II conjugation enzymes and membrane transporters. 14 Sweet potato (Ipomoea batatas L.) is an important food crop from the Convolvulaceae family that has about 6500 varieties worldwide. 15 The sweet potato plant tolerates flooding and is resistant to pests 16,17 and provides various nutrients that can compensate for malnutrition and vitamin deficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…, quercetin) can lower B[ a ]P-induced toxicity by increasing the expression of phase II conjugation enzymes and membrane transporters. 14…”
Section: Introductionmentioning
confidence: 99%